How to write the statement #S_1,S_2,S_3#? Thanks!

enter image source here

1 Answer
Feb 16, 2018

We have:

# S_n: 1^2 + 4^2 + 7^2 + ... (3n-2)^2 = (n(6n^2-3n-1))/2 #

So then statements #S_1, S_2 and S_3# would be:

# S_1: 1^2 = (1(6-3-1))/2 #
# \ \ \ \ \ \ => 1 = 2/2 = 1 #, which is true .

# S_2: 1^2 +4^2= (2(24-6-1))/2 #
# \ \ \ \ \ \ => 1+16 = 18-1#, which is also true .

# S_3: 1^2 +4^2 + 7^2= (3(54-9-1))/2 #
# \ \ \ \ \ \ => 1+16 +49 = 66#, which is also true .

In general, we can prove the result is true using Induction:

Induction Proof - Hypothesis

We seek to prove that:

# sum_(k=1)^n \ (3k-2)^2 = (n(6n^2-3n-1))/2 # ..... [A]

So let us test this assertion using Mathematical Induction:

Induction Proof - Base case:

We will show that the given result, [A], holds for #n=1#

When #n=1# we have #S_1#, which we have already shown to be true/

So the given result is true when #n=1#.

Induction Proof - General Case

Now, Let us assume that the given result [A] is true when #n=m#, for some #m in NN, m gt 1#, in which case for this particular value of #m# we have:

# sum_(k=1)^m \ (3k-2)^2 = (m(6m^2-3m-1))/2 # ..... [B]

Consider the LHS of [A] with the addition of the next term, in which case we have

# LHS = sum_(k=1)^(m+1) \ (3k-2)^2 #
# \ \ \ \ \ \ \ \ = {sum_(k=1)^m \ (3k-2)^2 } + (3(m+1)-2)^2 #
# \ \ \ \ \ \ \ \ = (m(6m^2-3m-1))/2 + (3m+1)^2 \ \ \ # using [B]
# \ \ \ \ \ \ \ \ = (m(6m^2-3m-1) + 2(3m+1)^2)/3 #
# \ \ \ \ \ \ \ \ = (6m^3-3m^2-m + 2(9m^2+6m+1))/2 #
# \ \ \ \ \ \ \ \ = (6m^3-3m^2-m + 18m^2+12m+2)/2 #
# \ \ \ \ \ \ \ \ = (6m^3+ 15m^2+11m+2)/2 #
# \ \ \ \ \ \ \ \ = ((m+1)(6m^2+9m+2))/2 #
# \ \ \ \ \ \ \ \ = ((m+1)(6(m^2+2m+1)-12m-6+9m+2))/2 #
# \ \ \ \ \ \ \ \ = ((m+1)(6(m+1)^2-3m-4))/2 #
# \ \ \ \ \ \ \ \ = ((m+1)(6(m+1)^2-3(m+1)-1))/2 #

Which is the given result [A] with #n=m+1#

Induction Proof - Summary

So, we have shown that if the given result [A] is true for #n=m#, then it is also true for #n=m+1# (ie, #S_m => S_(m+1)#) where #m gt 1#. But we initially showed that the given result was true for #n=1# so it must also be true for #n=2, n=3, n=4, ... # and so on.

Induction Proof - Conclusion

Then, by the process of mathematical induction the given result [A] is true for #n in NN#

Hence we have:

# sum_(k=1)^n \ (3k-2)^2 = (n(6n^2-3n-1))/2 \ \ \ QED#